PENGARUH PENGGUNAAN MEDIA UNPLUGGED TERHADAP KEMAMPUAN BERPIKIR KOMPUTASIONAL SISWA KELAS VI PADA MATERI BUMI DAN ANTARIKSA: Penelitian Tindakan Kelas - Fani Rhofiqhohrahmah; Yuli Agustina; Neni Hermita; Rifqa Gusmida Syahrun barokah (STKIP Subang, 2026)
This study is motivated by the low computational thinking skills of elementary students due to conventional learning and limited use of innovative media, especially in abstract topics such as Earth and Space. This study aims to analyze the effect of unplugged media on sixth-grade students’ computational thinking skills. A quantitative pre-experimental design with One Group Pretest-Posttest was used. The sample consisted of 25 students selected through purposive sampling. Data were collected using pretest and posttest and analyzed using descriptive statistics, N-Gain, and paired t-test. The results showed that the average score increased from 68.4 to 93.6 with an N-Gain of 0.78 (high category), and the t-test indicated a significant difference (Sig. < 0.05). It can be concluded that unplugged media significantly improves students’ computational thinking skills and can serve as an innovative learning strategy in elementary education.